Limonoids from andiroba oil and Cedrela fissilis and their insecticidal activity - Ambrozin, Alessandra R. P. (2006)
Nine limonoids were isolated from Carapa guianensis and Cedrela fissilis. Among them, 1,2-dihydro-3β-hydroxy-7-deacetoxy-7-oxogedunin is a new compound. Moreover, the assignments of some chemical shifts of xyloccensin k have been corrected and 1H NMR data of 7-deacetylgedunin have been assigned for the first time. These isolated limonoids were assayed on Atta sexdens rubropilosa workers showing moderate insecticidal activities. ©2006 Sociedade Brasileira de Química.